Возможности медицинской техники при диагностике гемодинамики беременных - Красникова, С. А.; Дацок, О. М. (ХНУРЭ, 2011)
We studied the central hemodynamic parameters in pregnancies complicated by cardiovascular diseases. Distribution of cardiovascular disease in pregnant women causes the creation of modern instrumentation diagnostics and monitoring, aimed at improving methods of recording and processing of biomedical indicators, as well as the development of methods and techniques for processing of diagnostic indicators. Цель настоящей работы состоит в анализе возможностей современной инструментальной диагностики кровообращения беременных с сердечно-сосудистыми заболеваниями.
Keywords: инструментальная диагностика; ровообращение беременных